Knowledge transfer through the ATHENA Twinning project: remote sensing for cultural heritage - Hadjimitsis, Diofantos G.; Christofe, Andreas; Agapiou, Athos; Lysandrou, Vasiliki; Tzouvaras, Marios; Papoutsa, Christiana; Mamouri, Rodanthi-Elisavet; Mettas, Christodoulos; Evagorou, Evagoras G.; Themistocleous, Kyriacos; Lasaponara, Rosa; Masini, Nicola; et al. (My University, 2018)
The project aims to establish a “Remote Sensing Science Center for Cultural Heritage” in Cyprus. The Center foresees to support the current Cultural Heritage (CH) needs through the systematic exploitation of Earth Observation technologies. For the establishment of the center, the existing Remote Sensing and Geo-Environment Research Laboratory of the Eratosthenes Research Center (ERC) based at the Cyprus University of Technology (CUT), is twinned with internationally-leading counterparts from the EU, the National Research Council of Italy (CNR, through IMAA and IBAM) and the German Aerospace Centre (DLR). Through this network, the ATHENA twinning project strengthens the remote sensing capacity in cultural heritage at CUT’s ERC. The ATHENA project aim is knowledge transfer, achieved primarily through intense training activities (including virtual training courses, workshops and summer schools) with an ultimate scope to enhance the scientific profile of the research staff and to accelerate the development of research capabilities of the ERC as well as to promote Earth Observation knowledge and best practices intended for Cultural Heritage. The scientific strengthening and networking achieved in Cyprus through the ATHENA project, could be of great benefit for the entire Eastern Mediterranean Region bearing a plethora of archaeological sites and monuments urgently calling for monitoring and safeguarding.
Keywords: Remote sensing; Cultural heritage; Geo-environment research